The Mirage of Interfix or Infix in Yoruba Concatenative Morphology - Adekunle, Moses Adedire (NIU Journal of Humanities, 2020)
Yorùbá linguists do not agree on the attestation of infixes in morphological analysis of the language. This is because if one needs to consider and adhere strictly to the definition of infix as a linguistic term, infix has zero occurrence in Yoruba concatenative morphology. Awobuluyi’s recent works, most especially, Awobuluyi (2008), opts for interfixation instead of infixation. This paper understudied the most current works on the topic (Awobuluy 2008 and Taiwo 2011) and concludes that none of the two aforestated affixal morphological operations occur in Yoruba morphological analysis. We, therefore, account for the process through lexical reduplication. The study tries to give reasons for the non-feasibility of the two affixal processes in the language. We adopt the word syntax theory as well as descriptive analysis to expand upon our current position which is novel in the literature of the Yoruba morphological analysis. It is therefore evident from this paper that further and intensive researches need to be done on some established positions in the morphological aspect of the Yoruba language in the hope of assessing the suitability and validity of such positions. Keywords: Infix, Interfix, Concatenative Morphology, Reduplication and Mirage